Women Empowerment on Food Security for Sustainable Development - Rosalia, Amelia Choya Tia; Prasetyani, Dwi; Rahman, Yozi Aulia; Putri, Phany Ineke (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
successful sustainable development in a country. Food security is also one of the indicators of the success of sustainable development in a country. The role of women is one of the keys to increasing food security. Women are sometimes considered less involved, even though they play an important role in the family. The extensive literature on women's empowerment in the context of food security is limited. This study's contribution is to present a study using the semi-systematic literature review (SSLR) method, which screens articles from various trusted sources using ideas about women's empowerment and food security. The role of women is related to food security at the family to community level. This study's results indicate a consistent positive relationship between multiple ideas about women's empowerment and food security. This study provides new insights and is expected to benefit for other researchers looking at previous studies and seeing the prospects for research that can be done.